O ensino de metáforas em Língua Portuguesa para surdos bilíngues Libras-Português - Josiane Marques da Costa (2020)
This research aims at investigating how to teach metaphors in written Portuguese to Deaf bilinguals (Libras-Portuguese), when teaching Portuguese as second language. Therefore, assuming the notions of Conceptual Metaphor, Conceptual Fluency and Metaphorical Competence, and some previous work on metaphorical awareness in second language learning, we examined if being aware of the metaphorical mappings could facilitate the comprehension and the retention of figurative vocabulary in Portuguese by Deaf learners of Portuguese as a second language. This research is organized in three parts. First, we analyzed how figurative language is discussed in textbooks of Portuguese as a foreign language and in textbooks of Portuguese as a second language for the Deaf. Our analysis shows that only idiomatic expressions are taught in these textbooks, when it comes to figurative language. Moreover, we could not identify any activity on metaphors or for the development of metaphorical awareness and metaphorical competence. In the second part, we investigated how teachers of Portuguese as L2, who work with Deaf students, conceive the task of teaching metaphors and figurative language. To that end, we interviewed teachers that work in mainstream schools, in bilingual schools for the Deaf and in special education environments, in order to identify if they teach figurative language to their Deaf students and what teaching strategies are used. We also investigated their perceptions on the capacity of Deaf students to learn figurative language in Portuguese; and how good is the teachers’ knowledge about figurative language in Libras. The interviews showed that teachers do not teach metaphors to their Deaf students, although they believe that Deaf people could learn those expressions. Additionally, although the teachers do know some sign language, they do not know metaphors in Libras – if they did, it could help them to teach Portuguese metaphors to their Deaf students. Finally, in the third part, we investigated if teaching the notions of conceptual metaphor and metaphorical mappings could enhance learning and comprehension of metaphorical expressions in L2. Therefore, after conducting a quasi-experiment, we suggest that explicitly teaching the notion of conceptual metaphor can positively contribute to the learning of metaphorical expressions in Portuguese by Deaf students.